Defending Russell’s Theory of Definite Descriptions Against a Strawsonian Attack - Akter, Shamima (Philosophy and Progress, 2024)
Although Russell’s theory of definite descriptions is highlyappreciated in the area of philosophy of language, it has faced some objections from different angles. One of the major objections is known as the objection arising from incomplete definite descriptions. According to this objection, a speaker by his/her utterance of a sentence containing an incomplete definite description often succeeds in saying something true despite the fact that such a sentence always expresses a false proposition. This particular objection against Russell’s theory arises because of an ignorance concerning the distinction between the meaning of a sentence and the assertion made by a speaker by using that sentence in a particular context. To address this distinction between meaning and assertion Scott Soames’ theory concerning the connection between meaning and assertion has been adopted. With the help of this theory, it has been shown that the problem arising from incomplete definite descriptions does not pose a genuine threat to Russell’s theory. Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 317-336